Drive-By Mochi’s / Nurul Nazilah Zahari - Nurul Nazilah Zahari, Zahari (2020)
Drive-By mochi’s is a sole proprietorship. It is located at Pt, 462, Ground floor, Jalan Jambatan Sultan Yahya Petra, Kg Sireh, Kota Bharu, Kelantan, Darul Iman. I have chosen this location because it is a strategic location. The date of the business commencement is on 1st January 2020. This bakery will serve good food and drink to the customer. Drive-By mochi’s allows customers to get the high-quality services within reasonable prices. Drive-By Mochi is determined to become the best bakery in town. It is also a place where we will provide a comfortable atmosphere where the customer can receive a good quality of baked goods fresh from the oven with a very affordable price. Not just freshly baked goods, we also have coffee and juices to serve to our customers. Most importantly, our bakery has a drive through section where our customers can just get their food without having to park and queue in the bakery. It will give some advantage to me because others bakery does not have the drive through and it will show the differentiate with other bakery. Thus, our bakery also has an event space where customers can celebrate any event with their family and friends. My customers target is working people and students. Due to its busy area in Kota Bharu, there are a lot of people will come to our bakery. Working people who does not have the time to prepare their breakfast, can easily go to our drive through for a quick order. As for the students, they will come here for their short breaks between classes or even to have their breakfast with friends. If they love it, they would not hesitate to promoting our cafe to all their circles. For administrative or organizational expenditure, it will be cost around RM 76286.55, while marketing budget will be around RM 16737. In operation budget, including machines, equipment, raw materials and overhead expenses, it will be costs RM 26822.30. Our profit in 2020 will be estimated around RM 524,000. While our profitability in 2021 and 2022 is estimated to be RM 892,800 and RM 930,000.